Pendampingan dan Pelatihan Pembalajaran Tajwid Melalui Irama Lagu Bagi Guru Taman Pendidikan Al-Qur’an - Khusnan Iskandar; Saeful Anam (TAAWUN, 2024)
This service aims to assist TPQ (Taman Pendidikan al Qur'an) teachers in the embalming of Tajwid through the rhythm of songs. The service method used is Service Learning with a Direct learning model that is oriented towards explaining the material and discussing with the participants present. The results of the service show that: the teacher's ability to apply Tajwid learning to the rhythm of the song is very good, this can be seen from the teacher's ability to practice it independently. Second, the students are motivated in following the learning of tajwid with the rhythm of the song, this can be seen from the enthusiasm of the students in following and memorizing the notes and rhythms given by the teacher.